Dark songs : slave house and synagogue : poems - Lieberman, Laurence (University of Arkansas Press, 1996)
Laurence Lieberman writes poems that successfully utilize techniques from every possible form of literature - including histories, travelogues, short stories, and epics. All the while, his lines maintain a deft balance of lyrical intensity, clear, methodical description, and the pure dialect of the characters living his poetry. In Dark Songs: Slave House and Synagogue, Lieberman creates a narrative mosaic of the eastern Caribbean islands, ranging from St. Eustatius in the eighteenth century to the island of Grenada after the United States-led invasion in 1983. When he writes of African slaves, British governors, Dutch Jews, island guerillas, fallen Swiss nobility, and piratelike charter captains, the wealth of his details, the force, and often the truth behind his stories allow us to witness the whole human saga of the Caribbean.